The nutritional and technological quality of common bean is affected by water stress and cultivar - Anderson Prates Coelho; Rogério Teixeira de Faria; Leandro Borges Lemos; Luiz Fabiano Palaretti; Fábio Tiraboschi Leal; Fábio Luiz Checchio Mingotte (Scientia Agricola, 2025)
ABSTRACT Agricultural management practices such as cultivar choice and irrigation management may change common bean technological and nutritional quality and affect the product price and food biological value. This study aimed to explain and compare the technological and nutritional grain quality of different common bean cultivars under various irrigation levels. The study was carried out for two years in the southeast of Brazil, including two common bean cultivars: IAC Imperador, which has a determinate growth habit, and IPR Campos Gerais, which possesses an indeterminate growth habit. Both cultivars were subjected to five irrigation levels: 54, 70, 77, 100, and 132 % of the crop evapotranspiration (ETo). Overall, cultivar IPR Campos Gerais had superior technological and nutritional quality compared to IAC Imperador. Specifically, its grain size were up to 119 % larger, had cooking time (CT) up to 36 % shorter, and contained higher levels of essential nutrients for human consumption, including P (up to 37 % higher), Mg (14 %), Fe (27 %), and Cu (18 %). Water deficit conditions reduced P, Ca, Mg, Cu, Mn, and Fe contents in the grains, with decreases of up to 22, 35, 6, 11, 5, and 5 %, respectively. The extend of these effects varied depending on the year and the cultivar. Moreover, water deficit promotes grains with up to 22 % more protein and 11 % more Zn. These results demonstrate the importance of proper irrigation management and cultivar choice to enhance common bean quality, leading to greater market acceptance and biological value as food.